(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the development of pan-Arab culture and political changes in the Arab world since the mid-19th century, called “Nahda” (renaissance). The creation of new Arabic literature, the development of education and the development of new ideological guidelines were carried out, “Nahda” was interpreted as a comprehensive development, the creators of “Nahda” considered the main task to restore the economic, political and cultural power of the Arabs, and also tried to synthesize elements of Western and Eastern culture.